2021
DOI: 10.19028/jtep.08.2.53-62
|View full text |Cite
|
Sign up to set email alerts
|

Kinetika Pengeringan Lapisan Tipis Daun Jati Belanda (Thin Layer Drying Kinetics of Guazuma Ulmifolia Leaves)

Abstract: The objectives of this study were to determine a suitable thin layer drying model to describe the drying kinetics of Guazuma ulmifolia leaves and determine the mass transfer parameters of Guazuma ulmifolia leaves. The drying of Guazuma ulmifolia leaves was conducted in a laboratory scale dryer with various temperature (40oC, 50oC, and 60oC) and relative humidity (30%, 40%, 50% and 60%). Five drying models, namely, Newton, Henderson and Pabis, Page, Midilli-Kucuk, and Verma et al. were fitted to the drying data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…This value is included in the effective moisture diffusivity of food and leafy specimens (10 -12 to 10 -8 m/s 2 ) [21]. This finding follows the results of earlier investigations on the P. niruri and P. amarus herbs drying [8], purple basil leaves [13], and Guazuma ulmifolia leaves [14]. A temperature rise induces a lowering in water viscosity and fluid outflow resistance [18].…”
Section: Effective Diffusivity and Activation Energysupporting
confidence: 84%
See 3 more Smart Citations
“…This value is included in the effective moisture diffusivity of food and leafy specimens (10 -12 to 10 -8 m/s 2 ) [21]. This finding follows the results of earlier investigations on the P. niruri and P. amarus herbs drying [8], purple basil leaves [13], and Guazuma ulmifolia leaves [14]. A temperature rise induces a lowering in water viscosity and fluid outflow resistance [18].…”
Section: Effective Diffusivity and Activation Energysupporting
confidence: 84%
“…In addition, it had previously been reported that most products only experience a falling-rate period affected by heat and mass transfer rate, which causes moisture to move to the surface of the material, experiencing evaporation [18]. According to several studies on the drying of some herbal leaves, no steady drying rate was observed; instead, a falling-rate drying [11]; [18]; [13]; [14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Rozana et al, 2016). The graph of the drying rate shows changes that are not constant, because at the beginning of drying there is no free water on the surface of the material (Syah et al, 2020). Two main factors that affect the drying process are the drying air factor and the material itself.…”
Section: Figure 17 Drying Rate Graphmentioning
confidence: 99%